Identifying critical incentives for scaling out the adoption of agroecological practices–a systematic review of Peruvian cacao value chains - Mockshell, Jonathan; Omulo, Godfrey; Asante-Addo, Collins; Nielsen Ritter, Thea; Quintero, Marcela; Remans, Roseline (Informa UK Limited, 2025)
The growing global importance of agroecology highlights the pivotal role public and private sectors play in providing incentives and investments to catalyze behavioural changes and transform food systems. However, limited research exists on incentives for scaling agroecological practices in cacao value chains. This study employed a systematic review approach, focusing on Peruvian cacao sector, to explore incentives promoting agroecological practices and their sustainability outcomes. Findings reveal that within Peru’s cacao value chains, non-market incentives constitute the majority (36%), followed by regulatory measures (25%), market-based incentives (22%), and cross-compliance incentives (17%). Main providers of incentives include certification bodies, community-based organizations, and international funding organizations. Effective incentives include sustainability standards, market support subsidies, in-kind rewards, and agroecological schemes that support the adoption of practices such as intercropping, nature conservation for carbon sequestration, and the use of green and animal manure. These incentives have significantly improved sustainability outcomes: economic (39%), environmental (33%), and social (28%). However, limited use of cross-compliance incentives and modest emphasis on social outcomes highlight the need for policy instruments targeting the adoption of agroecological practices within cacao sector. This study provides insights for policymakers, development agencies, and private-sector to design effective incentives for advancing agroecological transitions in Peru and beyond.